Hypogammaglobulinemia and Infection Events in Patients with Autoimmune Diseases Treated with Rituximab: 10 Years Real-Life Experience - Nie, Yuxue; Zhang, Nianyi; Li, Jingna; Wu, Di; Yang, Yunjiao; Zhang, Li; Bai, Wei; Jiang, Nan; Qiao, Lin; Huang, Can; Zhou, Shuang; Tian, Xinping; et al. (Journal of clinical immunology, 2024)
Objectives To investigate predictors of hypogammaglobulinemia (HGG) and severe infection event (SIE) in patients with autoimmune disease (AID) receiving rituximab (RTX) therapy. Methods This was a retrospective study conducted in a tertiary medical center in China. Predictors of HGG or SIE were assessed using Cox analysis. Restricted cubic spline (RCS) analysis was applied to examine the correlation between glucocorticoid (GC) maintenance dose and SIE. Results A total of 219 patients were included in this study, with a cumulative follow-up time of 698.28 person-years. Within the study population, 117 patients were diagnosed with connective tissue disease, 75 patients presented with ANCA-associated vasculitis, and 27 patients exhibited IgG4-related disease. HGG was reported in 63.3% of the patients, where an obvious decline in IgG and IgM was shown three months after RTX initiation. The rate of SIE was 7.2 per 100 person-years. An increase in the GC maintenance dose was an independent risk factor for both hypo-IgG (HR 1.07, 95% CI 1.02–1.12, p = 0.003) and SIE (HR 1.06, 95% CI 1.02–1.1, p = 0.004). Further RCS analysis identified 7.48 mg/d prednisone as a safe threshold dose for patients who underwent RTX treatment to avoid a significantly increased risk for SIE. Conclusion HGG was relatively common in RTX-treated AID patients. Patients with chronic lung disease or who were taking ≥ 7.5 mg/d prednisone during RTX treatment were at increased risk for SIE and warrant attention from physicians.